Faculty development and student learning : assessing the connections - Condon, William, 1950- (Bloomington : Indiana University Press, 2016)
"Colleges and universities across the US have created special initiatives to promote faculty development, but to date there has been little research to determine whether such programs have an impact on students' learning. Faculty Development and Student Learning reports the results of a multi-year study undertaken by faculty at Carleton College and Washington State University to assess how students' learning is affected by faculty members' efforts to become better teachers. Extending recent research in the Scholarship of Teaching and Learning (SoTL) to assessment of faculty development and its effectiveness, the authors show that faculty participation in professional development activities positively affects classroom pedagogy, student learning, and the overall culture of teaching and learning in a college or university"--Back cover.
Foreword: Pathways from faculty learning to student learning and beyond / Mary Taylor Huber -- Connecting faculty learning to student learning -- Sites of faculty learning -- Seeking the evidence -- Faculty learning applied -- Spreading the benefits -- Reaching students -- Faculty development matters -- Afterword: Afterward / Richard Haswell.
Includes bibliographical references.
Print version record.
Keywords: College teachers -- In-service training; EDUCATION -- Higher; College teachers -- In-service training; Electronic books; Electronic books